Analysis of bleb morphology after trabeculectomy with Visante anterior segment optical coherence tomography - Leung, Christopher Kai‐shun (BMJ Group, 2007)
BACKGROUND: To describe the use of anterior segment optical coherence tomography (OCT) in imaging intrableb morphology after trabeculectomy. METHODS: 14 post‐trabeculectomy eyes from 11 primary open angle glaucoma and 3 primary angle closure glaucoma subjects were studied. The blebs were classified with reference to slit lamp morphology and bleb function. They included diffuse filtering (n = 7), cystic (n = 2), encapsulated (n = 2) and flattened (n = 3) bleb types. One eye in each patient was imaged with the Visante anterior segment OCT. A vertical scan line of 10 mm consisting of 512 A‐scans was positioned at the centre of the bleb. The images were then analysed by built‐in software. Intrableb morphologies and structures, including bleb wall thickness, subconjunctival fluid collections, suprascleral fluid space, scleral flap thickness, intrableb intensity (low, medium or high) and the route under the scleral flap were characterised and measured. RESULTS: Diffuse filtering blebs were found by subconjunctival fluid collections. Suprascleral fluid space and the route under the scleral flap were identified in four of the seven cases. Cystic blebs were composed of a large hyporeflective space with multiloculated fluid collections covered by a thin layer of conjunctiva. Encapsulated blebs had a thick bleb wall with high reflectivity and an enclosed fluid filled space. Flattened blebs demonstrated high scleral reflectivity and no bleb elevation. CONCLUSIONS: Visante anterior segment OCT can be used for bleb imaging. The different patterns of intrableb morphology identified by OCT were related to slit lamp appearance and bleb function. This information may be useful to study the different surgical outcomes and the process of wound healing in trabeculectomised eyes.